Konfigurasi Sistem ERP dengan Odoo pada UMKM Nafara Store - Muhammad Nabil (KALBISIANA Jurnal Sains, Bisnis dan Teknologi, 2022)
MSME Nafara Store is a store engaged in the food sector since 2011 which is located on Jl. Panti Asuhan Gg. A1 RT 12/RW 04 No.22 Jatinegara District, East Jakarta. MSME Nafara Store provides food or drinks that can be enjoyed with family or friends but MSME Nafara Store has problems such as recording data still using manual methods then sales invoices are still often lost and not computerized, information for product sales and purchases is still very minimal so from Therefore, this research was made using Odoo with the waterfall method in order to facilitate the performance of the Nafara Store SMEs.